Hand and torso pre-cooling does not enhance subsequent high-intensity cycling or cognitive performance in heat. Issue 2 (2nd April 2020) - Maroni, Tessa; Dawson, Brian; Landers, Grant; Naylor, Louise; Wallman, Karen
ABSTRACT: The purpose of this study was to compare the separate and combined effects of two practical cooling methods (hand and torso) used prior to exercise on subsequent high-intensity cycling performance in heat. Ten trained male cyclists (V̇O2 peak: 65.7 ± 10.7 ml.kg −1 .min −1 ) performed four experimental trials (randomised within-subjects design) involving 30-min of pre-cooling (20-min seated; PRE-COOL, 10 min warm-up; PRE-COOL+WUP), while using a: (1) hand-cooling glove (CG); (2) cooling jacket (CJ); (3) both CG and CJ (CG+J); or (4) no-cooling (NC) control, followed by a cycling race simulation protocol (all performed in 35.0 ± 0.6°C and 56.6 ± 4.5% RH). During the 30-min of pre-cooling, no reductions in core (Tc) or mean skin temperature (Tsk) occurred; however, Tsk remained lower in the CJ and CG+J trials compared to NC and CG (p = 0.002–0.040, d = 0.55–1.01). Thermal sensation ratings also indicated that participants felt "hotter" during NC compared to all other trials during both PRE-COOL and PRE-COOL+WUP (p = 0.001–0.015, d = 1.0–2.19), plus the early stages of exercise (sets 1–2; p = 0.005–0.050, d = 0.56–1.22). Following cooling, no differences were found for absolute Tc and Tsk responses between trials over the entire exercise protocol (p > 0.05). Exercise and cognitive (working memory) performance also did not differ between trials (p = 0.843); however, cognitive performance improved over time in all trials (p < 0.001). In summary, pre-cooling (20-min seated and 10-min warm-up) in heat did not improve subsequent high-intensity cycling performance, cognitive responses and associated thermoregulatory strain (Tc and Tsk) compared to control.